2022
DOI: 10.3389/fmicb.2022.901865
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Tolerant PGPR Confer Salt Tolerance to Maize Through Enhanced Soil Biological Health, Enzymatic Activities, Nutrient Uptake and Antioxidant Defense

Abstract: Salt-tolerant plant growth-promoting rhizobacteria (PGPR) can improve soil enzyme activities, which are indicators of the biological health of the soil, and can overcome the nutritional imbalance in plants. A pot trial was executed to evaluate the effect of inoculation of different salt-tolerant PGPR strains in improving soil enzyme activities. Three different salinity levels (original, 5, and 10 dS m–1) were used and maize seeds were coated with the freshly prepared inocula of ten different PGPR strains. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 70 publications
(76 reference statements)
4
16
0
Order By: Relevance
“…Notably, multiple groups of root-associated microbes, including plantgrowth-promoting rhizobacteria (PGPR) and endophytic bacteria, are essential to improve plant tolerance to high salinity (Figure 3) (Qin et al, 2016;Vives-Peris et al, 2018). PGPR alleviates the toxicity of salt stress on plants mainly by regulating ionic homeostasis, accumulating osmolytes, activating antioxidant capacity, and enhancing essential nutrient uptake (Santos et al, 2018;Ha-Tran et al, 2021;Shabaan et al, 2022). For instance, a recent study suggested that the bacterial strain E. cloacae PM23 mediated salt tolerance in maize by modulating plant physiology, antioxidant defense, and compatible solute accumulation (Ali et al, 2022).…”
Section: Microbiota and Plant Salt Tolerancementioning
confidence: 99%
“…Notably, multiple groups of root-associated microbes, including plantgrowth-promoting rhizobacteria (PGPR) and endophytic bacteria, are essential to improve plant tolerance to high salinity (Figure 3) (Qin et al, 2016;Vives-Peris et al, 2018). PGPR alleviates the toxicity of salt stress on plants mainly by regulating ionic homeostasis, accumulating osmolytes, activating antioxidant capacity, and enhancing essential nutrient uptake (Santos et al, 2018;Ha-Tran et al, 2021;Shabaan et al, 2022). For instance, a recent study suggested that the bacterial strain E. cloacae PM23 mediated salt tolerance in maize by modulating plant physiology, antioxidant defense, and compatible solute accumulation (Ali et al, 2022).…”
Section: Microbiota and Plant Salt Tolerancementioning
confidence: 99%
“…Several studies have discovered that endophytic bacteria are important in alleviating salt stress in a range of agricultural plants [ 16 , 17 ]. For instance, PGP endophytic bacterium Cronobacter sp.…”
Section: Introductionmentioning
confidence: 99%
“… Akram et al (2016) also reported that some bacterial isolates from maize tolerate higher salinity levels and most of the bacterial growth was inhibited at a higher level of NaCl. Similarly, Shabaan et al (2022) also reported the existence of salt-tolerant PGPR conferring salt tolerance in maize plants.…”
Section: Discussionmentioning
confidence: 85%